Heterosexist discourse in adult education: A gay/lesbian critique - Robert J. Hill (Adult Education Research Conference, 1994)
Heterosexism is a widely-shared system that assumes heterosexuality is the only life option. The result is the domination of members of lesbian, gay, bisexual, transgendered and transsexual communities. Gay resistance discourse exposes this hegemony and is an agent for social change. Adult education plays roles in both heterosexist- and gay-discourses in at least two significant ways. Mainstream adult education reproduces heterocentric social relations and beliefs; gay discourse is silenced and forgotten. However, numerous sites of popular adult education promote gay and lesbian liberation.